Micro Enterprises Management Based On Islamic Paradigm - Syafrida Hani; Azuar Juliandi; Irfan Irfan; , Elizar Sinambela (International Journal Reglement & Society (IJRS), 2022)
This study aims to describe how micro business management is based on the Islamic paradigm. This is related to the Micro Business Strategy to Obtain Allah's Pleasure. The results of the study are expected to contribute to minimizing the problems faced, including limited human resources, capital, low ability to manage finances, lack of innovation and mastery of information technology. the main goal in developing the Islamic economy and in accordance with the objectives of the Islamic maqashid. Likewise with business management in Islam which aims to manage natural resources and all of their contents so that they can be utilized and benefit others, managed and processed properly and not contrary to Islamic law. Business management in Islam should be based on 1) the principle of monotheism and organizational commitment; 2) principles of organizational science and learning; 3) moral principles and personality of members of the organization; 4) principles of worship and work practices; 5) the principle of mardhatillah and performance